Młodzi dorośli z niepełnosprawnością wobec zadań rozwojowych i życiowych wyborów – w poszukiwaniu jakości życia codziennego1 - Suchodolska, Jolanta (Kultura-Społeczeństwo-Edukacja, 2019)
Emerging adulthood, in numerous individual biographies, also in the case of disabled people, is the time of permanent need for self-actualisation and time of verifying one’s subjective vision of “being an adult,” i.e. being responsible for one’s own decisions, pursuing professional and economic independence. Due to developmental acceleration, sociological shift in terms of undertaken roles and realized developmental tasks as well as their moratoriumlinked delays, it is also the time conducive to educational activity. This psychological time of a young person, its course and specificity depend, to a large extent, on numerous (micro-, mezo- and macro-) conditions of family life and social life in today’s world which is more competitive and less predictable than it used to be for generation of the late 1990s. All of these factors contribute to the fact that maturing to adulthood seems to be a state which is harder to achieve nowadays. It is displayed in the form of delaying the moment of taking up a job or other important decisions in family and relationship contexts. The study aims to present the selected aspects of daily life of disabled young adults, described in the context of developmental tasks of this period and considering the perspective of investment in relationships, development of one’s own resources, pursuing education and entering the job market which are all, from a temporal perspective, a chance of complementing one’s own identity.